2020
DOI: 10.1007/s12145-020-00505-1
|View full text |Cite
|
Sign up to set email alerts
|

Rock classification in petrographic thin section images based on concatenated convolutional neural networks

Abstract: Rock classification plays an important role in rock mechanics, petrology, mining engineering, magmatic processes, and numerous other fields pertaining to geosciences. This study proposes a concatenated convolutional neural network (Con-CNN) method for classifying the geologic rock type based on petrographic thin sections. Herein, plane polarized light (PPL) and crossed polarized light (XPL) were used to acquire thin section images as the fundamental data. After conducting the necessary pre-processing analyses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 34 publications
0
21
0
2
Order By: Relevance
“…Knaup (2019) indicates that, in her experience, deeper models suffer from overfitting problems and demonstrates that a 5-layer model outperforms the 7-layer model. For thin section classification tasks, Su et al (2020) also report that increasing model depth from 5 to 50 layers does not result in higher accuracies.…”
Section: Application Of Convolutional Neural Network In Petrographic Datamentioning
confidence: 89%
“…Knaup (2019) indicates that, in her experience, deeper models suffer from overfitting problems and demonstrates that a 5-layer model outperforms the 7-layer model. For thin section classification tasks, Su et al (2020) also report that increasing model depth from 5 to 50 layers does not result in higher accuracies.…”
Section: Application Of Convolutional Neural Network In Petrographic Datamentioning
confidence: 89%
“…The analysis and evaluation of performance and productivity of valuable rock resources mining, in particular, asbestos mining in an open pit, is one of the priority tasks in the mining industry [1][2][3][4][5][6]. As a rule, the estimation of performance (productivity) in an open pit is carried out either visually or in the stationary laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the known engineering solutions in the mining industry has shown that contemporary computer vision systems allow the automation of such mining processes as coal and rocks classification on the conveyor [2]; the rocks and coal sorting by size [1] and types [3]; the ore size determination [4]; the fossil identification and classification in ore [8]; the asbestos fiber size estimation under microscopy [9]; and other tasks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations